(untitled) (Human Factors in Design, 2023)
3D-printed prostheses are affordable and contribute to rehabilitation, but they have limitations. The grip is crucial to improving functionality. In this study, different materials were tested for adherence, applying them in different positions, and observing sliding with weights in a cylindrical grip. The Latex material obtained the best performance, applied to the digital, phalanx, and palm. Increasing adherence contributes to the experience, satisfaction, and acceptance of users of these prostheses. This drives Assistive Technology and related fields forward.